Análise de impactos ambientais gerados pela implantação de loteamentos fechados de alto padrão - Pereira, João Henrique [UNESP] (2015)
As the population of the cities are increasing and the economic growth of developing countries, urbanization has been changing drastically the limits of the new cities. Moreover, the areas of these cities have been growing quickly and unconsciously. Consequently, these cities are facing serious problems such as floods, more vehicles, deforestation and domestic garbage. In the southeast region, as well as in other regions in the country, construction companies prefer transforming big rural areas in closed allotments. This is due to the safety that they provide, which make sales more easily and the value of this enterprise also grows. The goal of this study is to evaluate the environmental impacts generated by this kind of enterprise, aiming their numerical representation, and, therefore make their analysis easier. The material used for developing this work was the Environmental Impact Study (EIS) and the Environmental Impact Report (EIR) of the enterprise, besides some bibliographies related to the theme and monitor of the construction and environmental monitoring programs suggested. For the numerical representation of the environmental impacts were created weights to its indicators and factors which had the objective of the study, to obtain the weights that characterized each environmental indicator, an analysis of the damage that each provide the environment was made, if it occurred alone and then there was interaction between them a matrix based on the Leopold matrix was applied. Some factors were created to represent the probability of occurrence of each event and the effectiveness of mitigation measures for each of the listed environmental impacts, so the analysis becomes more complete and realistic, resulting in a more reliable numerical representation. At the end of the study can be seen that the objective of this research was reached once did a representation of environmental impacts of easy analysis and good reliability was obtained